Develop a mathematical model of a chain of trench excavator - A. L. Ahtulov; L. N. Ahtulova; V. A. Osit (Вестник СибАДИ, 2017)
The article presents a series of mathematical models of individual subsystems and the analysis of the simulation chain of trench excavator on the basis of which the generalized mathematical model to determine the key parameters in the design of the control device volumetric hydraulic transmission of attachments digging under a chain of trench excavator. The substantiation of criterion of efficiency of application of chain of trench excavator for the process of dissection and undermining of the pipeline.